Gender Disparity and Socio-Demographic Characteristics of Adolescents in Northern Nigeria - James, Godswill; Akpokos, James Amos (European Journal of Sustainable Development, 2013)
This paper gives insights into the adolescents’ socio-economic and demographiccompositions and brings to limelight the various issues that affect their wellbeing. It alsoprovides available data that can be translated into meaningful information which can beused to establish guidelines for the development of appropriate policies and programmesfor the welfare of adolescents. The present study was conducted in three states in North-Western Zone of Nigeria, namely Kaduna, Kano and Katsina. These states have thehighest total percentage of teenagers who have begun child bearing in the North-Westzone, more than half of the total projected population of the zone and about 60% of thetotal projected population of teenagers age 12-19 in the zone. Questions relating to use ofmethods of contraception were also asked. Data on knowledge and use of contraceptivemethods are central to demographic analysis particularly fertility phenomenon. This studyhighlighted the immediate need for a concerted effort towards solving the severalproblems confronting the adolescents in northern Nigeria.